Identification of Salmonella Bredeney Resistant to Third-Generation Cephalosporins in Saudi Arabia - Al kraiem, Ayman Ahmad; Zeng, Yingchun; Huo, Xixiang; Yang, Kun; Al kraiem, Fahd; Qin, Jingliang; Cui, Yujun; Kan, Biao; Yan, Meiying; Yang, Guang; Chen, Tie (Frontiers in Cellular and Infection Microbiology, 2019)
The rapidly increasing prevalence and spread of antibiotic-resistant Salmonella throughout the world have become a thorny problem that poses a serious threat to human health. It is speculated that the abuse of antibiotic usages and high density of human traveling and Mass Gatherings (MGs) accelerate this threat. To explore the hypothesis, 13 Salmonella isolates from Mecca area of Saudi Arabia and 15s from China as the control group were performed with the typical methods of serotype identification, antibiotic resistance tests, pulsed-field gel electrophoresis (PFGE) and multi-locus sequence typing (MLST). Our results presented that the isolates from China showed greater serotype diversity and a higher antimicrobial resistance rate, which were consistent with results in other studies from China. In contrast, the Saudi Arabian isolates were mainly identified as Serovar Bredeney and resistant to very limited antibiotics. To a biggest surprise, one of the Bredeney isolates was resistant to third-generation cephalosporins but sensitive to all other tested antibiotics. To confirm the results and understand the underlying molecular mechanisms of these isolates, a whole genome sequencing (WGS) was performed. We found that several cephalosporins resistance-associated fragments were shared with other strains, but one sequence (LEN-23) was very unique to this strain. Therefore, we concluded that this study, for the first time, reported the emergence of Salmonella Bredeney resistant to third-generation cephalosporins in Saudi Arabia.